Ras family signaling pathway in immunopathogenesis of inflammatory rheumatic diseases - Sadeghi Shaker, Mina; Rokni, Mohsen; Mahmoudi, Mahdi; Farhadi, Elham (Frontiers in Immunology, 2023)
The Ras (rat sarcoma virus) is a GTP-binding protein which considered one of the substantial membranes of the Ras-GTPase superfamily. The Ras involves several pathways in the cell that include proliferation, migration, survival, differentiation, and fibrosis. Abnormalities in the expression level and activation of the Ras family signaling pathway and its downstream kinases such as Raf/MEK/ERK1-2 contribute to the pathogenic mechanisms of rheumatic diseases including immune system dysregulation, inflammation, and fibrosis in systemic sclerosis (SSc), destruction and inflammation of synovial tissue in rheumatoid arthritis (RA), auto-antibodies production and immune complexes formation in systemic lupus erythematosus (SLE), and enhances osteoblast differentiation and ossification during skeletal formation in AS. In this review, the basic biology, signaling of Ras, and abnormalities in this pathway in rheumatic diseases including SSc, RA, AS, and SLE will be discussed.